Tellurite glasses for microstructured optical fibers manufacturing - Stepien, Ryszard; Buczynski, Ryszard; Pysz, Dariusz; Kujawa, Ireneusz; Mirkowska, Monika (Photonics Letters of Poland, 2010)
Two series of tellurite glasses synthesized in a TeO2-WO3-PbO-Na2O-Nb2O5 oxide system with variable contents of WO3 (5÷38mol%) and PbO (0÷18mol%) are designed and manufactured. Their transmission properties, thermal expansion coefficients and glass characteristic temperatures have been determined. The glasses with the highest resistance to recrystallization during thermal treatment have been selected. Fiber drawing tests are performed and confirmation of the usefulness of these out glasses in the manufacture photonic crystal fibers is obtained. Full Text: PDF References: T.M.Monro and H.Ebendorff-Heidepriem, "Progress in Microstructured Optical Fibers", Rev. Mater. Res. 36, 467-495 (2006). [CrossRef] D.Lorenc, M.Aranyosiova, R.Buczynski, R.Stepien, I.Bugar, A.Vincze, D.Velic, "Nonlinear refractive index of multicomponent glasses designed for fabrication of photonic crystal fibers ", Applied Physics B: Lasers and Optics, 93, 531-538 (2008). [CrossRef] V.V.Ravi Kanth Kumar, A.K.George, J.C.Knight, and P.S.J. Russell, "Tellurite photonic crystal fiber", Opt. Express 11, No 20, 2641-2645 (2003). [CrossRef] D.A.Gaponov, A.S.Biryukov, "Optical properties of microstructure tellurite glass fibres", Quantum Electron 36(4), 343-348 (2006). [CrossRef] E.F.Chillcce, C.M.B.Cordeiro, L.C.Barbosa, C.H. Brito Gruz, "Tellurite photonic crystal fiber made by a stack-and-draw technique ", J.Non-Cryst.Solids 352, 3423-3428 (2006). [CrossRef]